Poteri signorili e feudali nelle campagne dell'Italia settentrionale fra Tre e Quattrocento: fondamenti di legittimità e forme di esercizio. Atti del convegno di studi Milano, 11-12 aprile 2003 - Federica Cengarle (Reti Medievali E-Book, 2005)
This volume contains the proceedings of the study convention held in Milan on 11 and 12 April 2003. The objective of these study days was to address the question of the powers of lordship which were exercised in the countryside of central-northern Italy between the mid fourteenth century and the end of the fifteenth century. The discussions focused on what instruments and what foundations of legitimacy these same powers had and what was their relationship with the authority of the prince and with the ordinary citizen, on the one hand, and with the community and the homines on the other. These and various other issues thrown up by the study of feudal power are the topics which emerge in the various contributions gathered in this volume, devoted principally to the Lombardy of the Visconti and the Sforza, but also to other areas of Italy.